2015
DOI: 10.1680/adcr.13.00083
|View full text |Cite
|
Sign up to set email alerts
|

Characterising cement carbonation curing using non-contact electrical resistivity measurement

Abstract: Carbonation curing of cement paste and concrete promotes early strength gain, improves durability and recycles carbon dioxide in a beneficial manner. To examine the carbonation curing mechanism, fresh cement pastes and concretes subject to carbonation are characterised using a non-contact electrical resistivity measurement method.Resistivity measurements reveal that characteristic features of the hydration accelerated by carbonation are different from conventional hydration. The typical induction period is abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Nevertheless, these methods are currently confined to laboratory settings and are inherently destructive, rendering them unsuitable for large-scale structures and critical components in engineering projects. Recently, non-destructive testing methods have been applied to the study of concrete carbonation, such as non-linear ultrasonic techniques [ 21 ], resistivity measurement [ 22 , 23 ], and electrochemical impedance spectroscopy [ 24 ], etc. Kim used a non-contact air-coupled transducer to detect Rayleigh wave signals and obtained the nonlinear parameters of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these methods are currently confined to laboratory settings and are inherently destructive, rendering them unsuitable for large-scale structures and critical components in engineering projects. Recently, non-destructive testing methods have been applied to the study of concrete carbonation, such as non-linear ultrasonic techniques [ 21 ], resistivity measurement [ 22 , 23 ], and electrochemical impedance spectroscopy [ 24 ], etc. Kim used a non-contact air-coupled transducer to detect Rayleigh wave signals and obtained the nonlinear parameters of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Morshed et al (2015) used a NC-ERM to investigate the hydration process of fresh mixes of cement pastes and concretes, and characterise the intake of CO 2 into hydration by the precipitation reaction. The authors observed the final resistivity of carbonation-cured samples was three to six times higher (pastes) and eight to 16 times higher (concretes) than the normally cured samples.…”
mentioning
confidence: 99%